Problems of a magistracy development in the conditions of higher education reforming - Larisa V. Konstantinova (Moscow Polytechnic University, 2022)
The article reviews the trends in Master's education in the light of the current higher education reform in Russia. The article analyzes various approaches to understanding of the specifics of Master's programs. It also discusses the challenges that the multi-level system of higher education experiences in the current labor market in Russia.